Application of Game Theory principles in the oligopoly-characterized industry - Strážnický, Matúš; Hořejší, Bronislava, 1955-; Šumpíková, Markéta, 1970-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
The goals of the master thesis are describing the strategic oligopoly environment of chosen industry of Czech telecommunications, together with introducing basic game theory principles with their possible real case application. It mentions historical shifts in Czech telecommunications sector which influence the actual industry conditions. The thesis briefly describes the individual players in the market and turns its attention towards the industry characterization through standard oligopoly models. Following, it introduces theoretical insight on possible market entry strategies into oligopoly industries. The application part focuses on game-theory in pricing strategies, market entry and entry deterring scenarios with examples. Final part summarizes the objectives in detail and provides final comments on the thesis.
Vedoucí práce: Bronislava Hořejší
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses